Peran Komunikasi dalam Membangun Kesadaran Hukum Islam Bagi Warga Negara Muslim - Ahmad Muhammad Mustain Nasoha; Ahfiya Nur Atqiya; Fina Fitria Nugroho; Davynna Nooraini Immawati; Coreana Akashi Nur Utami (Pemuliaan Keadilan, 2025)
Communication has an important role in building awareness of Islamic law among Muslim citizens. Through effective communication, Islamic legal norms and rules can be understood, internalized and applied in everyday life. This article discusses the role of communication in increasing awareness of Islamic law by analyzing various communication approaches, such as da'wah, education, and social media. By using literature review methods from various scientific sources, it was found that modern communication media, such as social media, are increasingly playing a role in conveying the message of Islamic law to the younger generation. In addition, persuasive and educational da'wah has proven to be an effective means of increasing understanding and compliance with sharia law. However, challenges such as disinformation on social media remain obstacles that need to be overcome with digital literacy based on Islamic values.